The Harmful Effects of Pesticides on the Environment and Human Health: A Review - Ali , Israa Mahmood (Diyala Agricultural Sciences Journal, 2023)
The population inflation that countries are witnessing during this century, makes it imperative to provide sufficient quantities of agricultural products to meet their urgent needs. Therefore, it became very necessary to use pesticides to improve agricultural crop productivity and reduce losses resulting from agricultural pests. The indiscriminate use of pesticides causes severe risks not only on agricultural fields, but also workers in their manufacturing processes and individual use in homes and institutions. The main adverse effects of utilizing pesticides on human health, soil, microorganisms of soil, surface water and groundwater have been covered in this review. This investigation is aiming to elevate environmental awareness, highlight the serious harms of pesticides and provide guidance for implementing a serious solution from the people and authorities. In addition, the most important strategies to reduce the pesticides risks have been summarized.